Comprehensive deterrence theory: the science and policy of punishment - Mears, Daniel P. (Cambridge University Press, 2025)
"This book offers a comprehensive understanding of classical deterrence theory, its limitations, and presents a new, reconceptualized account of how legal punishment can deter crime. Ideal for scholars, researchers, policymakers, and the general public, the book includes recommended chapter sequences, examples, and a new theory to improve policy"--